The Effect of Foreign Liability, Interest Coverage Ratio and Growth Opportunity on Hedging Decisions with Leverage as a Moderating Variable - Halimah Miranty Prassida; Tiara Syaharani (Yayasan Az Zukhruf Cendikia, 2026)
Objective – This study aims to examine the effect of Foreign Liability, Interest Coverage Ratio, and Growth Opportunity on hedging decisions, with Leverage as a moderating variable. Design/methodology/approach – This study employs a quantitative approach using logistic regression analysis. The sample consists of 44 non-primary consumer goods sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Findings – The results show that Foreign Liability has a negative and statistically significant effect on hedging decisions, indicating that companies with higher foreign currency liabilities tend to reduce their hedging activities. This finding contrasts with the initial hypothesis that predicted a positive relationship and represents a unique empirical result. The Interest Coverage Ratio has a negative but insignificant effect, while Growth Opportunity has a positive and significant effect on hedging decisions. Furthermore, Leverage significantly strengthens the relationship between Foreign Liability and hedging decisions but does not moderate the effects of Interest Coverage Ratio and Growth Opportunity. Originality/value – This study contributes to the hedging and risk management literature by providing empirical evidence from the non-primary consumer goods sector in Indonesia during the most recent period and highlighting the contrasting role of Foreign Liability in hedging decisions. JEL : G34, M14, J16, Q56